Plan de negocios para la creación de una empresa de elaboración y comercialización de bolsas, bolsos y accesorios ecológicos en el sector Bosa de Bogotá (2021)
The objective of this work is to carry out a business plan for the creation of a company for the production and commercialization of ecological bags, handbags and accessories in the Bosa sector in Bogotá, to reach customers who correspond to commercial establishments that for the commercialization of their products use plastic packaging or bags and who wish to make a change towards biodegradable bags in order to contribute to mitigating the environmental impact generated by plastic on this planet; For this purpose, an innovative and striking line is thought of, made with jute; that differs from other products of this style by its elegance that makes it an accessory that can be worn. Likewise, it is proposed with the development of the business plan to recognize if it is feasible to establish the company dedicated to the economic activity previously exposed in the city in question.